Depletion of Complement Has Distinct Effects on the Primary and Secondary Antibody Responses to a Conjugate of Pneumococcal Serotype 14 Capsular Polysaccharide and a T-Cell-Dependent Protein Carrier - Test, Samuel T. (American Society for Microbiology, 2005)
Complement activation plays a critical role in the immune response to T-cell-dependent and T-cell-independent antigens. However, the effect of conjugation of T-cell-dependent protein carriers to T-cell-independent type 2 antigens on the requirement for complement in the humoral immune response to such antigens remains unknown. We studied the role of complement activation on the antibody response of BALB/c mice immunized with the T-cell-independent type 2 antigen serotype 14 pneumococcal capsular polysaccharide (PPS14), either in unmodified form or conjugated to ovalbumin (OVA). In mice immunized with either PPS14 or PPS14-OVA, depletion of endogenous complement at the time of primary immunization by treatment with cobra venom factor (CVF) diminished serum anti-PPS14 concentrations after primary immunization but enhanced antibody responses after secondary immunization. The secondary immunoglobulin G (IgG) anti-PPS14 antibody response after immunization with PPS14-OVA was especially enhanced by complement depletion, was observed at doses as low as 0.2 μg of antigen, and was maximal when CVF was administered within 2 days of immunization. The avidity and opsonophagocytic functions of IgG anti-PPS14 antibodies were comparable in mice immunized with PPS14-OVA with or without complement depletion. Serum anti-PPS14 antibody concentrations were near normal, and the enhancing effects of CVF treatment on the secondary anti-PPS14 antibody response were also apparent in splenectomized mice immunized with PPS14-OVA. These results demonstrate that complement activation can have distinct effects on the primary and secondary antibody responses to a T-cell-independent type 2 antigen, either unmodified or conjugated to a T-cell-dependent protein carrier. These differences should be taken into consideration when using complement to modulate the immune response to vaccines.